Chemical compositions and antioxidant activity of Heracleum persicum essential oil - Maryam Gharachorloo; Masoud Honarvar; Shima Mardani (Universidade de São Paulo, 2018)
ABSTRACT In this study essential oil of the aerial parts of Heracleum persicum a spice widely used in Iran was isolated by conventional hydrodistillation (HD) and microwave-assisted hydrodistillation (MAHD) techniques. The extraction yield was determined and the chemical compositions of essential oils were identified by the application of gas chromatography/mass spectrometry (GC/MS). The antioxidant activity was determined by two different methods: 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging and oven test methods. Although the main compounds of essential oils by the both extraction methods were similar, the essential oil extracted by HD with lower extraction efficiency showed more diverse compounds. The evaluation of antioxidant activity of the essential oil measured by delay in sunflower oil oxidation indicated that the antioxidant activity was dependent on the concentration which increased when higher concentrations of the essential oils were applied. The results of DPPH radical assay also indicated that the percentage of inhibition increased with increasing of essential oil concentration and IC50 value for essential oil extracted by MAHD method was obtained 1.25 mg/mL. Therefore the Heracleum persicum essential oil might be recommended for use as a flavoring agent and a source of natural antioxidants in functional foods, formulation of the supplements and in medicinal due to numerous pharmacological activities.